Investigation on in-vitro Dissolution and Tableting Properties Enhancement of Etodolac using Stearoyl polyoxyl-32-glycerides as Novel Solid Melt Carrier - Salunkhe, Pradnya; Gurav, Prashant B; Sansare, Vipul; Nagare, Sujit (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: The objective of present study was to improve dissolution rate with tableting properties of BCS class II drug Etodolac, by melt granulation and sublimation techniques. Materials and Methods: The granules of etodolac were formulated using Gelucire 50/13. The surface adsorbent Aerosil 200 was utilized. Both melt granulation and surface adsorption method in conjunction with sublimating agent were used to formulate tablets of Etodolac. Etodolac: Gelucire 50/13: Aerosil200 was used in different ratio for melt granulation technique to improve dissolution and tableting properties. Results: Solubility study of melt granules were carried out in different ratio. 1:2:1 ratio showed 25 fold increases in solubility of Etodolac. This 1:2:1 (A4) ratio was selected to designate the tablets along with super disintegrant and sublimating agents. Precompression and postcompression parameters results were satisfactory for etodolac tablets. XRD and DSC study showed that Etodolac crystallinity was completely disappeared in A4 melt granules. In vitro drug release of formulation F4 and F8 containing crosscarmallose sodium and menthol were found to be 94.64% and 98.14% drug release at the end of 24 and 20 min respectively. The dissolution statistics like MDT, %DE and DP10 for optimized formulation F8 exhibited 8.90 min, 28.25% and 55.45% respectively. Conclusion: The melt granulation technique is useful to improve dissolution of Etodolac ideally, along with superior tableting properties.
Keywords: Etodolac; Gelucire50/13; Melt granulation; Sublimating agent; Surface; adsorption; Dissolution improvement